Metode Ekstraksi Sarang Semut (Myrmecodia Pendans) dengan Teknik Maserasi untuk Menghasilkan Obat Alternatif Kanker Paru - Suharyanto; Purwono, Bambang (Jurnal Farmasi (Journal of Pharmacy), 2015)
Cancer is a growing cells of any type of cell and tissue in the body anywhere, a large number of diseases are characterized by tissue and cell type of origin. Each year found nearly 6 million new patients known to have cancer, and more than 4 million of them died. Until now cancer treatment is done by 3 ways: surgery, radiation, and drug delivery of anti -neoplastic or anti- cancer. However, all three treatments over a lot of side effects to the patient. This study aims to conduct a series of pre-clinical trials to determine the optimal dose of Sarangsemut plant ( Myrmecodia pendens ) can be used as a drug to cure lung cancer. The specific objective of this research is to extract Sarangsemut plant ( Myrmecodia pendens ) and soursop leaves to produce drugs alterlatif cancer disease. Benefits of this research can be used.